A comparison of the calculated profile drag coefficients of various low drag wing sections - Dowlen, E. M. (College of Aeronautics, Cranfield, 1950)
The profile drag-coefficients of a number of low-drag wings with straight trailing edges have been calculated. A comparison is made with other low-drag and conventional sections which indicates an increase in profile drag, for a given transition point position, with rearward movement of the position of maximum velocity and with increase of trailing edge angle. Some experimental results obtained at low Reynolds number are included for comparison. A shortened method of calculating the profile drag coefficient of an aerofoil is developed.